Synthesis and Characterization of a Molecularly Imprinted Polymer for Diclofenac Sodium Using (2-vinylpyridine and 2-hydroxyethyl metha acrylate) as the Complexing Monomer - Baghdad Science Journal (مجلة بغداد للعلوم)
Four electrodes were synthesized based on molecularly imprinted polymers (MIPs). Two MIPs were prepared by using the diclofenac sodium (DFS) as the template, 2-hydroxy ethyl metha acrylate(2-HEMA) and 2-vinyl pyridine(2-VP) as monomers as well as divinyl benzene and benzoyl peroxide as cross linker and initiator respectively. The same composition used for prepared non-imprinted polymers (NIPs) but without the template (diclofenac sodium). To prepared the membranes electrodes used different plasticizers in PVC matrix such as: tris(2-ethyl hexyl) phosphate (TEHP), tri butyl phosphate (TBP), bis(2-ethyl hexyl) adipate (BEHA) and tritolyl phosphate (TTP). The characteristics studied the slop, detection limit, life time and linearity range of DFS–MIPs electrodes. The results were obtained from selectivity measurements on amino acids showed good response as well as pharmaceuticals analysis.